A fibromialgia e a dor crônica: o tratamento pelo exercício físico e a influência de componentes biopsicossociais no entendimento da dor - Franco, Katherinne Ferro Moura (2019)
The main objective of this study was to evaluate the effectiveness and cost-effectiveness of exercises in the modified Pilates method compared to aerobic exercises in the treatment of patients with fibromyalgia. For this, in this randomized controlled study, 98 patients who met the 2010 American College of Rheumatology classification criteria for fibromyalgia, aged between 20 and 75 years, and with pain intensity ≥ 3 points on the Numerical Pain Scale, were randomly assigned. divided into Aerobic Group (aerobic exercises on treadmills and/or stationary bicycles) or Pilates Group (modified Pilates exercises) and treated twice a week for eight weeks at the Center of Excellence in Clinical Research in Physiotherapy of the University of the City of São Paul. The following outcomes will be assessed by a blind evaluator at baseline, eight weeks, six months and 12 months after randomization: impact of fibromyalgia (Fibromyalgia Impact Questionnaire), pain intensity (Numerical Pain Scale), kinesiophobia (Scale Kinesiophobia Cap), specific disability (Patient Specific Functional Scale), functional capacity (6-minute walk test), sleep quality (Pittsburgh Sleep Quality Index) and health-related quality of life (EQ-5D and SF-6D). As a result it was found that there was a statistically significant difference in favor of the Pilates group for pain after 8 weeks (mean difference [MD]: 1.2 points, 95% confidence interval [CI]: 0.0 to 2.3), sleep quality after 6 months (MD: 1.9 points, 95% CI: 0.5 to 3.3) and health-related quality of life after 12 months (MD: 0.07; 95%CI: -0.1 to -0.00). The cost-utility analysis showed that Pilates appears to be the preferred option for the EQ-5D, but not for the SF-6D. The secondary objectives of this study were: to summarize existing evidence on exercise prescription for patients with chronic pain (fibromyalgia, disorders associated with chronic whiplash injury and idiopathic neck pain); compare different health state utility instruments in Brazilian patients with fibromyalgia and define variables that are associated with these instruments; assess how much psychological symptoms influence pain intensity and level of disability in patients with fibromyalgia; and assess the presence of body image distortion in patients with fibromyalgia. To summarize the evidence on exercise prescription for fibromyalgia, disorders associated with chronic whiplash injury, a systematic review was performed. The search was conducted at the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (Pubmed), EMBASE, CINAHL and PEDro. Data related to the type of physical exercise, characteristics and parameters for pain management were extracted for analysis. Fifty randomized controlled trials with 3562 participants were included in the qualitative synthesis and 24 studies were included in the meta-analysis. For Fibromyalgia: There is very poor quality evidence that aerobic exercise appears to be better than just stretching exercises. There seems to be no difference between performing aerobic exercises on land or in a swimming pool. However, there is poor quality evidence that aerobic exercise appears to be similar to strengthening exercises and muscle strengthening appears to be better than stretching exercises. Regarding exercise prescription, supervised sessions, with 50 to 60 minutes, 2 to 3 times a week, for a treatment period of 13 weeks or more, can be used in patients with fibromyalgia. For disorders associated with chronic whiplash injury: Only two studies were included and showed that body awareness exercises are similar to the combination of aerobic exercise + strengthening + coordination. And it makes no difference to add sling exercises to the combination of muscle strength + muscle endurance exercises. Supervised sessions twice a week for up to 90 minutes for a treatment period of 10 to 16 weeks can be used in these patients. For chronic idiopathic neck pain: there is poor-quality evidence that combined exercise appears to be better than meditative therapies, and motor control exercises appear to be similar to nonspecific muscle strengthening. And supervised sessions, 30 to 60 minutes in duration, 2 to 3 times a week, for a period of 7 to 12 weeks of treatment can be used for these patients. To compare different health status utility instruments in Brazilian patients with fibromyalgia, a secondary analysis of a randomized controlled trial was performed. In this study, 97 patients with fibromyalgia were evaluated. The outcomes analyzed were the impact of fibromyalgia (Fibromyalgia Impact Questionnaire), and utility indices (Short Form 6 Dimensions - SF-6D, EuroQol 5 Dimensions - EQ-5D, and EuroQol - Visual Analog Scale - EQ-EVA), eight weeks, six and 12 months after randomization in a randomized controlled trial with economic evaluation. Utility indices were compared in an analysis of convergent validity and responsiveness. Multiple regression models were used to verify variables that could be associated with the utility instruments. As a result, the analysis of convergent validity showed that there was a moderate correlation between the EQ-5D and SF-6D instruments with the impact of fibromyalgia (r=-0.410; r=-0.393 respectively), and a weak correlation for the EQ-EVA (r=-0.324). There is a strong correlation between EQ-5D and SF-6D (r=0.534), weak between SF-6D and EQ-EVA (r=2.97) and there was no correlation between EQ-EVA and EQ-5D (r=0.191 ). In the responsiveness analysis, it was observed that EQ-5D was responsive at the eight-week and six-month assessments, SF-6F was responsive only at six months, and EQ-EVA was not responsive. Multiple regression analysis showed that only the impact of fibromyalgia was related to the EQ-5D and SF-6D scores, and the duration of pain and depression was related to the EQ-EVA score. To verify the association between high levels of pain and disability and the presence of psychological factors in patients with fibromyalgia, a cross-sectional study was carried out, in which the following outcomes were evaluated in 104 patients with fibromyalgia: pain (Numerical Pain Scale), disability (Patient-Specific Functional Scale), depression (Beck Depression Scale), anxiety (State-Trait Anxiety Inventory), kinesiophobia (Capital Kinesiophobia Scale), pain catastrophizing (Pain Catastrophizing Scale), beliefs and attitudes towards pain (Inventory of Attitudes to Pain) and the occurrence of abuse at some point in life. Statistical analysis was performed using linear regression models. As a result, it was observed that high levels of depression were associated with high levels of pain intensity (0.07; 95% CI: 0.02 to 0.11; p = 0.00), and high levels of kinesiophobia were associated to high levels of disability (-0.06; 95% CI: -0.09 to -0.02; p = 0.00). Depression can explain 10% of pain intensity, while kinesiophobia can explain 9% of disability. To assess whether there is body image distortion in patients with fibromyalgia, and whether there is body image modification in these patients after exercise, a cross-sectional study and a secondary analysis of a randomized controlled trial were performed. The following outcomes were evaluated in 24 fibromyalgia patients and 24 asymptomatic participants: pain (Numerical Pain Scale), body image (Drawing and Two-Point Discrimination Test), and limb circumference (cirtometry). After evaluation, patients with fibromyalgia were allocated to the following groups: Aerobic Exercise and Pilates. Our results showed that there was no significant difference in the body image of the cervical (4.7 mm; 95% CI: -23.6 to 33.1), lumbar (11 mm; 95% CI: -40.3 to 62.4 ), hands (-3.6 mm; 95% CI: -3.6 to 62.4) and feet (-8.3 mm; 95% CI: -21.9 to 5.1) among participants with fibromyalgia and asymptomatic. However, patients with fibromyalgia had their body image altered by comparing the drawings with cirtometry. After the intervention, there was no significant difference between aerobic exercise and Pilates for pain (0.42 mm; 95% CI: -1.8 to 2.7) and for cervical body image (11.3 mm; 95% CI : -16 to 38.6), lumbar (3.1 mm; 95% CI: -12.4 to 18.6), hands (-0.9 mm; 95% CI: -12.9 to 11.2 ) and feet (0.9 mm; 95% CI: -17.4 to 19.2) in patients with fibromyalgia.